RANCANG BANGUN ALAT PENGATUR KERUCUT LALU-LINTAS SEMI-OTOMATIS - Christiand Christiand; Reinaldo Khowanto; Makdin Sinaga (University of Muhammadiyah Jakarta, 2018)
The management (pick and place activities) of traffic cones (KLL) is generally performed in traditional way where the operator of KLL management picks and places KLL by using their body power. Therefore, the speed and effeciency of the task greatly depends on the power, stamina, and skill of the operator. Furthermore, in the case of KLL management at toll roads, the speed of task completion may vary because of stamina decreasing and huge number of KLL. Improving the speed and efficiency of the task is absolutely needed. One of the goals is to reduce the time of task completion as well as the power consumption of the operator. Electric motor may be used as the solution to achieve faster and effective KLL management. In this research work, a semi-automatic KLL pick-n-place machine is proposed to solve the problem. This machine uses DC motor to reduce the human power. In addition, a semi-automatic controller is designed to reduce the human role in the work sequence of KLL pick-n-place machine. Mechanical design of the machine is carefully formulated by taking into account the aspects of carrier (truck) type and the strength of build-material. The concept of the design is simple yet tough. The machine is designed to be flexible in mounting position whether it is mounted in the left or right side of the carrier deck. From the experiment, the maximum speed of the carrier when managing the KLL was ± 10 km/hour.